Quality Indicators in Palliative Radiation Oncology: Development and Pilot Testing - Tetsuo Saito, MD, PhD; Naoto Shikama, MD, PhD; Takeo Takahashi, MD, PhD; Misako Miwa, MD, PhD; Kazunari Miyazawa, MD; Hitoshi Wada, MD, PhD; Naoki Nakamura, MD, PhD; Atsunori Yorozu, MD, PhD; Hisayasu Nagakura, MD; Mitsunori Miyashita, RN, PhD (Advances in Radiation Oncology, 2022)
Purpose: A quality indicator (QI) is a valuable tool to evaluate the quality of health care systems. In palliative radiation oncology, only a few related QIs have been developed to date. In this study, we sought to develop and pilot test QIs that assess the quality of care in palliative radiation therapy. Methods and Materials: A modified Delphi method was used to establish consensus with an expert panel. The panel consisted of 8 radiation oncologists who have expertise in palliative radiation oncology and 1 expert on Delphi methodology. Online panel meetings and e-mail surveys were conducted to develop QIs on palliative radiation therapy for bone and brain metastases. Feasibility of measurement was assessed though pilot surveys that were conducted by radiation oncologists at 5 facilities. Results: After 3 online meetings and 2 e-mail surveys, we developed 4 QIs on bone metastases and 3 QIs on brain metastases. Two email surveys and 2 pilot surveys confirmed the validity of QIs and the feasibility of measurement, respectively. Conclusions: We developed valid and feasible QIs on palliative radiation therapy for bone and brain metastases. Our work may contribute to reduce the evidence–practice gaps in palliative radiation oncology.